Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors. (10th February 2023) - Su, Xiaoli; Sun, Feiyun; Zhang, Jianjun; Xing, Dingyu; Li, Xiaoying; Song, Zi; Feng, Liang; Huang, Zhichao; Li, Ang
Abstract: This study investigated the interaction between function microbiota succession and three electron acceptors in anaerobic sulfamethoxazole (SMX) degradation. Over 20%–60% SMX was degraded biologically after antibiotics acclimation under co-electron acceptors. Under sulfate- and nitrate-reducing conditions, SMX removal followed a pseudo-zero-order kinetic model and related to the sludge adsorption site. Microbiological analyses showed syntrophic community, including autotrophic denitrifiyer, nitrate reducing-sulfate oxidizier, and heterotrophic denitrifier, were putative SMX reducers. As an electron acceptor, sulfate was more beneficial in degrading SMX and maintaining the system stability and the colony structure. However, autotrophic nitrate-reducing sulfate-oxidizing bacteria has a stronger substrate competition advantage than sulfate-reducing bacteria (SRB), resulting in invalid SMX degradation. Thus, for the system start-up, SRB and iron/sulfur-based denitrifier should be preferentially enriched with sulfate electron acceptors to assure the removals of antibiotics. These results uncovered crucial factors that may affect the fate of SMX and associated biochemicals in anaerobic degradation processes but were previously overlooked. Graphical abstract: Image 1 Highlights: SMX removals by anaerobic bacteria related closely with bulk redox conditions. SMX biodegradation fits well the modified the pseudo-zeroth order under various conditions. SMX resistant/tolerant chemoautotrophic bacteria predominated for all conditions. Long-term SMX feeding favored sulfur-based chemoautotrophic mixotrophic denitrification.